OPSONIZING PROPERTIES OF A COMMERCIAL ANTISTAPHYLOCOCCAL IMMUNOGLOBULIN - S. V. Slobodchikova; K. V. Schmagel (Медицинская иммунология, 2014)
Abstract. Antistaphylococcal immunoglobulins (ASIg) are widely used for treatment of staphylococcal infections. However, Russian literature sources still lack any evidence-based data justifying clinical efficiency of this preparation. Taking into account a key role of phagocytosis for a macro-organism resistance to staphylococci, and importance of microbial opsonization in this response, a trial of antistaphylococcal immunoglobulinmediated opsonizing activity was performed with S. aureus Wood 46 and S. aureus Cowan I strains. A normal human Ig preparation was used as a reference substance. Both preparations influenced oxygen-dependent bactericidal effects of phagocytes to a similar degree. Normal immunoglobulin proved to be more active than ASIg, with respect to neutrophil ingestion properties and bacterial aggregation. Hence, present results, along with relevant data from Russian and foreign literature put in question the ASIg expediency for medication of staphylococcal infections.